The Influence of Organizational Culture on Organizational Citizenship Behavior through Organizational Commitment - Zati, Muhammad Nugraha; Aisyah, Siti; Hardjo, Suryani (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
A teacher in a school is a benchmark for the advancement of an educational institution. This is because the participation of educators is very influential in improving school efficiency and improving accreditation. When students have good achievements, school accreditation is also good, and cannot be separated from the performance of teachers. This study was conducted on vocational high school teachers to determine the effect of OCB on organizational culture through organizational commitment. This study is a quantitative study with a total sampling technique of 135 respondents. The data collection technique uses the OCB research scale, organizational culture and organizational commitment. The analysis method used in this study is quantitative descriptive, the analysis test tool used is SmartPLS v.3.0 with the SEM (Structural Equation Modeling) analysis method. Based on the results of this study, it shows that organizational culture has a significant and positive effect on OCB, organizational culture has a positive and significant effect on organizational commitment, organizational commitment has a positive and significant effect on OCB, organizational culture has a positive effect on OCB through organizational commitment.